The relationship between serum asymmetric dimethylarginine levels and radial artery spasm - Ibrahim Kocayigit; Mehmet Akif Cakar; Behlül Kahyaoğlu; Muhammed Necati Murat Aksoy; Ersan Tatli; Ramazan Akdemir (Anatolian Journal of Cardiology, 2020)
Objective: The use of the radial approach in coronary angiography or percutaneous coronary intervention has increased owing to its advantages over the femoral approach such as rapid patient mobilization and improved patient comfort. However, radial artery spasm (RAS) that occurs during the procedure is a crucial factor in transradial approach failure and access site switch. Asymmetric dimethylarginine (ADMA) is a naturally occurring, modified amino acid that inhibits nitric oxide (NO) production. High ADMA levels may reduce arterial elasticity especially in small arteries like the radial artery. This study aimed to evaluate the relationship between ADMA levels and RAS in radial artery access. Methods: This study included 155 patients (89 males and 66 females) who underwent transradial coronary angiography between January 2016 and June 2016. The ADMA level in the plasma was determined using a quantitative sandwich enzyme immunoassay technique. Results: RAS was observed in 16 of the 155 patients (10.1%). The RAS was found to be more frequent in female patients (17.9% for women vs. 4.4% for men, p=0.019). The plasma concentration of ADMA in the RAS group was significantly higher than that in the control group [22.1 ng/mL (12.1–37.8) vs. 9.2 ng/mL (5.9–14.8), p<0.001]. Moreover, the plasma concentration of ADMA was significantly higher in patients with RAS among female patients [20.4 ng/mL (12.1–44.9) vs. 9.9 ng/mL (6.2–16.6); p=0.002] and among male patients [25.2 ng/mL (13.7–35.4) vs. 8.2 ng/mL (5.9–12.8); p=0.007]. Binary logistic regression analysis of all patients showed that ADMA concentration was the only predictor for RAS (odds ratio=1.142; 95% confidence interval=1.061–1.228; p<0.001). Conclusion: It was found that the ADMA concentration of the patients in the RAS group was elevated compared to that of controls. The findings indicated that elevated ADMA concentrations could predict RAS that may occur.